Developing of fish anatomy learning module based on local wisdom in Ngebel Lake, Ponorogo, East Java - Cicilia Novi Primiani; Trio Ageng Prayitno; Egista Dinka (University of Muhammadiyah Malang, 2020)
The use of local wisdom as learning resources has been widely known to be able to create meaningful learning. The purposes of this study were to 1) produce module based on freshwater fish anatomy as local wisdom in Ngebel Lake, Ponorogo and 2) find the quality of the module produced. The Research and Development (R&D) was designed based on the Thiagarajan model which consisted of defining, designing, developing, and disseminating stages. The data were collected using interview guidelines, validation sheets, and students’ response questionnaire. The validation results of the media, material, and language experts showed that the module was very valid with the percentages were 86.5%, 88.2%, and 85.3% respectively. In addition, the student responses reached 87.9% (very good). In conclusion, the fish anatomy learning module based on local wisdom is appropriate to be used as learning resource.